Application of TDCG and Duval Triangle Methods for Diagnosing Internal Faults in Distribution Transformers (Jurnal Ampere, 2025)
Distribution transformers play a crucial role in maintaining continuity of electricity supply, especially in vital installations such as airports. This research was conducted at Sultan Mahmud Badaruddin II International Airport in Palembang from January to April 2025 with the aim of diagnosing the internal condition of transformers, identifying any disturbances occurring in the transformers, and recommending actions using the Dissolved Gas Analysis (DGA) method through the Total Dissolved Combustible Gas(TDCG) and Duval's Triangle approaches. The test results showed that in January and February 2025, the TDCG value was at Condition 2 (caution), indicating potential internal disturbances, while Duval's triangle analysis placed the transformer in zone T2 (thermal fault 300–700°C) with indications of arcing due to the emergence of acetylene gas. However, in March and April 2025, conditions improved, as indicated by a decrease in TDCG values to Condition 1 (Normal) and a shift in the Duval zone to T1 (mild thermal